The Plural is Unmarked: Evidence from Turkish, Hungarian and German - Artemis Alexiadou; Kazuko Yatsushiro; Uli Sauerland; Vasfiye Geçkin; Veronika Harmati-Pap (Glossa, 2023)
Quantity distinctions are morphologically indicated in the majority of languages.However, the marking of these distinctions exhibits a high degree of cross-linguistic variation with respect to the number of quantity categories, their agreement properties, and the morphemes themselves. Furthermore, number marking on numerically quantified nouns varies across languages: for instance, while German and English use plural number marking with numerals other than “one” (for example, “two books”), Turkish and Hungarian use singular number marking with all numerals. Recent work has discussed how to explain number marking with numerals. In particular, Bale and Khanjian (2014) propose that the quantity concepts of the two types of languages vary semantically. We present novel evidence from a cross-linguistic study of Hungarian, Turkish and German child language, and argue that the quantity concepts do not vary, and the variation between languages must have a morphosyntactic explanation.